The Influence of Price, Location, and Islamic Business Ethics on the Sales Level of Salsa Batang Shop, Indonesia - Widayah Widayah; Muhammad Taufiq Abadi (ProBisnis : Jurnal Manajemen, 2023)
The level of sales is the peak of a transaction result from marketing activities or also known as marketing carried out by a company in selling products and services offered to consumers. Various strategies are carried out by sellers in order to meet the expected level of sales. several factors that can lead to increased sales levels, such as Price, Location, and Islamic Business Ethics. This study aims to determine whether price, location, and Islamic business ethics can affect the level of sales at the Salsa shop, Ujungnegoro Village, Batang Regency.The method used in this study is a quantitative method by distributing questionnaires to Salsa shop consumers to obtain raw data. The number of samples is as many as 82 respondents. The sampling technique is carried out using the Nonprobability Sampling method, namely Convenience Sampling, which is then processed using SPSS 21 raw data. The results of this study are the price and Islamic business ethics variables have no effect on the level of sales, while the location variable has a positive and significant influence to the level of sales.